Foreign direct investment and institutional quality: international evidence - Tun, Yin Li; Wan Ngah, Wan Azman Saini; Law, Siong Hook (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This paper examines whether domestic institutional quality has any important role in attracting FDI. To test the hypothesis, data from 77 countries over the 1981-2005 period is utilised. Methodologically, this paper uses a system generalised method-of-moment panel estimator to address some of the weaknesses encountered in the previous literature on FDI-institution link. The empirical results demonstrate that institutions are significant determinant of FDI inflows. This finding is in line with the view that improvements in the quality of domestic institution will reduce the cost of doing business, reduce uncertainty, and improve productivity prospect. This will eventually lead to more investments. Importantly, the finding on the important role played by domestic institution in attracting FDI is robust and is not driven by outlier observations, or problems caused by weak instruments and simultaneity bias.